State of the art on immersive virtual reality and its use in developing meaningful empathy. (July 2021) - Estrada Villalba, Éder; San Martín Azócar, Alejandra Lorena; Jacques-García, Fausto Abraham
Highlights: Empathy is not just a trait and can increase or decrease in different situations. Perspective taking is more effective than providing data to feel empathy. Virtual reality can increase engagement and empathy concern and perspective taking. Virtual reality perspective taking could be more effective than traditional methods. Abstract: Empathy seems to have been one of the most relevant factors in examining the use of Virtual Reality (VR) in recent years. This technology allows users to embody someone else through virtual experiences, taking another's perspective and perceive their avatar's actions as their own. Thus, Perspective-Taking with Virtual Reality (PTVR) looks promising as an entry portal to promote or develop empathic responses. This article presents a state-of-the-art from the academic and scientific literature published between 2015 and 2020 on the use of VR to promote empathic capacity development, with attention to implementations in educational contexts (although not exclusively). Findings include trends about the use of VR to promote empathic responses and how previous studies have carried out experimentations. We discuss empathy measurement and the lack of rigorous, empirical, scientific evidence to ensure that VR could be the vehicle for developing empathy, as many would wish. Graphical abstract: Image, graphical abstract